Proposed new interior design scheme of Scott Retail at No.10A, Pusat Perdagangan Greentown,Greentown Avenue,31400 Ipoh Perak. / Nooraizah Abidin - Abidin, Nooraizah (Faculty of Architecture, Planning and Surveying, 2011)
A final year student of diploma course in Interior Design is required to prepared one final year project. Its compulsory requirements to get a scroll of diploma. The selection of the project must be related to current issues to help student succeed. The knowledge and skills are required along the process of design works which includes research, case study, interviewing, designing a proposal, submission by stages, create session, preparing art work, preparing presentation drawings, design development and final presentation. The project that had been chosen for the final project is to proposed a Scott Retail for Rodalink at No. 10 A, Pusat Perdagangan Greentown, Greentown Avenue, 31400 Ipoh, Perak. The reason to propose this project is because to design the different retail with others in Malaysia. The proposal is for opening a new branch for the accessories bike. It also to add more retail which sell bicycle accessories and introduce new product especially from international. The proposed new Scott Retail provides a new disclosure of the internal design functions. With a mission to introduce and organize Scott Retail in proffesional way to advanced with formulating proposals to increase existing display retail to show the concept of Scott Retail which carries the objectives of systematic planning and work for every space without the expense of needs, requirements and customer comfort. The target market for the users of this Scott Retail are children from age 18 until adult that not know basic about product scott. The main objective is to introduce a ‘from line to masterpiece’ concept and image ‘modern’ design to follow the client corporate image and identity. The were several researches done to succeed this Scott Retail final project, amongst them are site analysis, building analysis, interview, and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear.